An Empirical Investigation on the Determinants of the Capital Structure of US Listed Firms - SHILIANG, LU (2009)
This paper is an empirical investigation of capital structure behaviour of 419 US firms. One of the aims is to evaluate which theory, trade-off theory or pecking order hypothesis, is better explaining the capital structure of selected firms. Moreover, this paper uses data that offers the unique opportunity to investigate whether September 11 tragedy impacts on the capital structure of selected firms. The sample used consists of all non-financial S&P500 firms in September 2008. The results show that different measures of debt level lead to different conclusions about the relationship between determinants and capital structure behaviour. The capital structure behaviour of selected firms could not be explained by either single theory. September 11 tragedy does impact on firms’ capital structure behaviour. It changes the signs of coefficients and relative importance of capital structure determinants.